Pengaruh Fungsi Audit Internal, Kompleksitas Perusahaan, Dan Risiko Perusahaan Terhadap Fee Audit - Iffah Humaira; Efrizal Syofyan (Universitas Negeri Padang, 2020)
This study aims to determine the effect of internal audit function, company complexity, and company risk on audit fees. The population in this study were Manufacturing companies listed on the Indonesia stockExchange (IDX) in 2015 to 2018. The research sample was determined using a purposive sampling method, and a total sample of 46Manufacturing companies. The data used is secondary data. Data collection techniques with documentation at www.idx.co.id . The analytical method used is Regression Analysis with Random Effect Model (REM). The results showed that (1) the internal audit function, company complexity, and company risk simultaneously have a significant effect on audit fees, (2) the internal audit function had not significant effect on audit fees, (3) company complexity had a positive and significant effect on audit fees, and (3) company riskhad not significant effect on audit fees.